Factors influencing the scope of private party's obligations in concession-based PPP projects in Nigeria. Issue 3 (11th July 2016) - Opawole, Akintayo; Jagboro, Godwin Onajite
Abstract : Purpose: – Little success had been recorded on concession-based public private partnership contracts in Nigeria for reasons attributable in part to poor assessment of the socio-cultural and economic factors that contribute to the parties' costs while preparing contract packages. The purpose of this paper is to assess the factors which significantly influence the private party's obligations and costs in a concession-based contract thereby enhancing the robust assessment of contract packages when bidding by private investors. Design/methodology/approach: – The assessment was based on primary data obtained through questionnaire survey. Structured questionnaire was administered on professionals comprising architects, estate surveyors, quantity surveyors, engineers and builders, accountants/bankers/economists and lawyers who had been involved in concession-based contracts in the Southwestern Nigeria, selected using respondent-driven sampling approach. Factors evaluated were those identified through in-depth literature review and brainstorming of those pertinent to concession transaction in Nigeria. Data collected were analysed using descriptive statistics including mean, relative significance index, impact weighting and factor analysis. Findings: – Significant factors that influence private party's cost were found to be political interference, delay in land acquisition, variation to the contract and non-availability of supportive infrastructure. Originality/value: – Findings provided information for structuring concession contract for effective management of country-specific characteristics in concession contract. The understanding of the factors that affect private party's obligations and costs would guide effective assessment of concession contract in developing economies by foreign investors. Moreover, the study provided implication for the understating of country-specific factors affecting concession contract in Nigeria which would contribute to robust assessment of contract packages when bidding by private investors.